Public Policy Challenges in the Digital Age: Balancing Innovation, Governance, and Equity - Mokadam, Ebrahem; Musa, Hussein Gibreel; Kumalasari, Ana; Istighfaroh, Faridatul (Universitas Bojonegoro, 2025)
The rapid advancement of digital technologies has significantly transformed public administration, offering opportunities to enhance service delivery, transparency, and citizen engagement. However, this transformation presents critical challenges, particularly in balancing technological innovation with governance effectiveness and social equity. The digital divide, data privacy concerns, and regulatory gaps remain significant barriers to achieving inclusive digital governance. This study explores these challenges through a systematic literature review methodology, analyzing recent academic research from peer-reviewed journals and reputable sources. The review focuses on identifying trends, policy frameworks, and challenges related to digital governance, with a particular emphasis on equity and inclusivity. The findings reveal a growing reliance on data-driven decision-making and digital platforms to engage citizens, yet highlight persistent disparities in digital access among marginalized communities. Additionally, the study emphasizes the need for adaptive regulatory frameworks to address rapid technological advancements and cybersecurity concerns. The research underscores the importance of fostering public-private partnerships and inclusive policy strategies to ensure sustainable digital transformation. Based on the findings, it is recommended that governments adopt holistic and adaptive digital policies, invest in digital literacy programs, and develop infrastructure to bridge the digital divide. By addressing these challenges, governments can create an equitable and efficient digital governance ecosystem that serves the broader public interest